The role of the IFO business climate indicator and asset prices in German monetary policy - Elmer Sterken (Center for Economic Studies and ifo Institute (CESifo), 2004)
We analyze the role of forward-looking indicators, like the IFO business climate indicator and asset prices, in German monetary transmission. We show that the use of both the IFO indicator and asset prices improves the performance and interpretation of a Vector AutoRegression (VAR) model of German monetary transmission. First, we show that the Bundesbank responded more intensively to changes in the IFO indicator than to changes in GDP. Secondly, we address the role of housing and equity prices. We demonstrate that especially housing prices help to give a more accurate description of the recent history of German monetary policy.
Keywords: C82; C22; C53; 330; monetary transmission; IFO business climate survey indicator; house prices; equity prices; Geschäftsklima; Börsenkurs; Immobilienpreis; Transmissionsmechanismus; Geldpolitik; Schätzung; Deutschland